Hypertensive disorders in pregnancy as primary and associated indications for caesarean section - Parveen, Sabina; Jasmine (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Hypertensive disorders in pregnancy (HDP) are a group of conditions characterized by high blood pressure during pregnancy. This can include gestational hypertension, preeclampsia, eclampsia, and chronic hypertension with superimposed preeclampsia. The HDP elicits various adverse outcomes like preterm delivery, placental abruptions and increased rate of caesarean delivery. Hence, the present study was carried out to evaluate the frequency and associated indication of caesarean section (CS) in HDP. Methods: A retrospective study was carried out on 110 pregnant women with HDP for a period of one year. The patient’s details like mode of delivery and the indication of CS delivery were recorded. Results: The most common HDP was gestational hypertension in 76 (69.1%) and the mean age of the patients was 24.24±4.42 years. Out of 110 HDP cases, 97 had delivered through CS with a rate of 88.2%. The main indication for caesarean delivery was previous LSCS in 22 (22.68%) of the patients, followed by gestational hypertension in 18 (18.56%), severe preeclampsia in 11 (11.34%) and preeclampsia in 8 (8.25%). Conclusions: HDP are a significant factor in the negative outcomes experienced by both mothers and their babies. Routine pregnancy check-ups, early detection, immediate multifaceted treatment, and optimal time for delivery are crucial in reducing the frequency of complications and maternal mortality. Timely referral and management of these cases at specialized neonatal centers can significantly decrease perinatal mortality rates.